2022
DOI: 10.1097/mao.0000000000003672
|View full text |Cite
|
Sign up to set email alerts
|

Combined Arterial and Venous Phase Computed Tomographic Imaging of the Skull Base in Pulsatile Tinnitus

Abstract: Objective: To describe the demographic, clinical, and radiologic findings in a consecutive series of patients presenting with a chief complaint of pulsatile tinnitus (PT). Study Design: Retrospective review of 157 patients undergoing a combined arterial/venous phase computed tomographic (CT) imaging study. Setting: Tertiary referral center. Patients: Adult patients referred to neurotology faculty for evaluation of PT between 2016 and 2020. Interventions: Triple phase high-resolution arteriography/venography/ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…A retrospective review of 157 patients with an average body mass index of 30.0 undergoing combined arterial/ venous phase CT for evaluation of pulsatile tinnitus found that 79% of scans were abnormal, 31 with bilateral transverse sinus stenosis (TSS) seen in 38.9% and unilateral TSS found in 20.4% (whereby unilateral pulsatile tinnitus was ipsilateral to the side of TSS in 84.4% of patients). This study highlights the importance of recognising that IIH with TSS can be an important cause of pulsatile tinnitus, especially in obese patients.…”
Section: Role Of Medical Imagingmentioning
confidence: 99%
“…A retrospective review of 157 patients with an average body mass index of 30.0 undergoing combined arterial/ venous phase CT for evaluation of pulsatile tinnitus found that 79% of scans were abnormal, 31 with bilateral transverse sinus stenosis (TSS) seen in 38.9% and unilateral TSS found in 20.4% (whereby unilateral pulsatile tinnitus was ipsilateral to the side of TSS in 84.4% of patients). This study highlights the importance of recognising that IIH with TSS can be an important cause of pulsatile tinnitus, especially in obese patients.…”
Section: Role Of Medical Imagingmentioning
confidence: 99%